Ultrasensitive aptasensor using electrospun MXene/polyvinylidene fluoride nanofiber composite for Ochratoxin A detection - Al-Dhahebi, A.M. (Elsevier Ltd, 2022)
Ochratoxin A (OTA) has harmful effects to human and animal health; therefore, sensitive and selective detection of OTA is highly demanded. Herein, an ultrasensitive electrochemical aptasensor electrode comprising electrospun MXene/polyvinylidene fluoride (Ti3C2Tx/PVDF) nanofiber composite is presented. Addition of Ti3C2Tx up to 13 effectively increased the fiber diameter and lowered the Î²-phase of PVDF nanofibers, consequently lowering the charge transfer resistance. The nanofiber composite is then coated on the screen-printed carbon electrode to chemically functionalized with saline and aldehyde groups for efficient aptamer loading. The optimized aptasensor demonstrated sensitive detection of OTA over the dynamic concentration range from 1 fg mLâ1 to 1 ng mLâ1 with a limit of detection of 2.15 fg mLâ1 and quantification limit of 6.52 fg mLâ1, with high selectivity. The aptasensor could detect the OTA at femtogram per milliliter concentration in grape juice samples, demonstrating its enormous potential for OTA detection in food industry. Â© 2022 Elsevier Ltd